KRIM EKSTRAK BUAH MERAH (PANDANUS CONOIDEUS ) 10% SAMA EFEKTIFNYA DENGAN KRIM HIDROKUINON 4% DALAM MENCEGAH PENINGKATAN JUMLAH MELANIN KULIT MARMUT (CAVIA PORCELLUS) YANG DIPAPAR SINAR ULTRAVIOLET B - Dumaria, Corazon H.; Wiraguna, A AGP; Pangkahila, Wimpie (UNIVERSITAS SAM RATULANGI, 2018)
Abstract: This study was aimed to prove that administration of 10% redfruit extract cream could prevent the increase of skin melanin in guinea pig exposed to UVB and to compare this effect with 4% hydroquinone cream. This was a true experimental study using post test only control group design. Subjects were devided into three groups; each of 10 guinea pigs. Group 1, the control group, was exposed to UVB and applied with basic cream. Group 2 was exposed to UVB and applied with 4% hydroquinone cream. Group 3 was exposed to UVB and applied with 10% redfruit extract cream. The total dose of UVB was 390 mJ/cm2 given for 2 weeks. The amount of melanin was calculated using the percentage of the pixel area of melanin and was compared with the pixel areas of all epidermal tissues. The results showed that the highest percentage of melanin area was in group 1 (19.78%±3.79%). The percentage of melanin area in group 3 was 1.25%±0.76% meanwhile in group 2 was 0.85%±0.37%. There were signi-ficant differences in melanin percentage between the control group and group 2 as well as group 3 (P <0.05). There was no significant difference in melanin percentage between group 2 and group 3 (P >0.05). Conclusion: The 10% redfruit extract cream could prevent the increase of skin melanin in guinea pig exposed to UVB as effectively as the 4% hydroquinone cream.Keywords: redfruit extract cream, melanin, UVBAbstrak: Penelitian ini bertujuan untuk membuktikan efek pemberian krim ekstrak buah merah 10% dalam mencegah peningkatan jumlah melanin kulit marmut yang dipapar sinar UVB dan perbandingannya dengan krim hidrokuinon 4%. Jenis penelitian ialah eksperimental murni dengan post test only control group design. Sampel terdiri dari tiga kelompok dengan jumlah sampel 10 ekor marmut jantan tiap kelompok. Kelompok 1 yaitu kelompok kontrol, diberi paparan sinar UVB dan diolesi krim dasar. Kelompok 2 diberi paparan sinar UVB dan diolesi krim hidrokuinon 4%. Kelompok 3 diberi paparan sinar UVB dan diolesi krim ekstrak buah merah 10%. Dosis total UVB yaitu 390 mJ/cm2 diberikan selama 2 minggu. Jumlah melanin dihitung dengan persentase pixel luas area melanin dibandingkan dengan pixel seluruh jaringan epidermis. Hasil penelitian menunjukkan jumlah melanin tertinggi pada kelompok 1 (19,78± 3,79%) dan terendah pada kelompok 2 (0,85±0,37%), sedangkan jumlah melanin pada kelompok 3 di antara keduanya (1,25±0,76%). Terdapat perbedaan bermakna antara kelompok 1 dengan kelompok 2 dan 3 (P <0,05). Tidak terdapat perbedaan bermakna antara kelompok 2 dan 3 dalam mencegah peningkatan jumlah melanin (P >0,05 ). Simpulan: Krim ekstrak buah merah 10% dapat mencegah peningkatan jumlah melanin kulit marmut yang dipapar sinar UVB sama efektif dengan krim hidrokuinon 4%.Kata kunci: krim ekstrak buah merah, melanin, UVB